Hydrogen diffusion and trapping in nanocrystalline tungsten - Piaggi, Pablo M. (2015)
The hydrogen behavior in nanocrystalline W (ncW) samples with grain size of 5 and 10 nm is studied using Molecular Dynamics (MD) with a bond order potential (BOP) for the W-H system. The dependence of the hydrogen diffusion coefficient on grain size (5 and 10 nm) and hydrogen concentration (0.1 at.% < [H] < 10.0 at.%) is calculated. These data show that in all cases the hydrogen diffusion coefficient is lower for ncW than for coarse-grained samples. Trapping energies of grain boundaries are estimated and a broad distribution roughly centered at the vacancy trapping energy is found. Hydrogen diffusion results are interpreted within the trapping model by Kirchheim for nanocrystalline materials. The H-H interaction is evaluated and the possible formation of H2 is disregarded for the conditions in these simulations. Hydrogen segregation and trapping in grain boundaries for ncW is discussed, including extrapolations for micron-sized polycrystals.